Local versus general anaesthesia for carotid endarterectomy. - Rerkasem, K; Rothwell, P (2008)
BACKGROUND: Carotid endarterectomy reduces the risk of stroke in people with recently symptomatic, severe carotid artery stenosis. However, there are significant perioperative risks which may be lessened by performing the operation under local rather than general anaesthetic. This is an update of a Cochrane review first published in 1996, and previously updated in 2004. OBJECTIVES: To assess the risks of endarterectomy under local compared with general anaesthetic. SEARCH STRATEGY: We searched the Cochrane Stroke Group Trials Register (last searched December 2007), MEDLINE (1966 to April 2007) EMBASE (1980 to April 2007) and Index to Scientific and Technical Proceedings (ISTP, 1980 to April 2007). We also handsearched six relevant journals to April 2007, and searched the reference lists of articles identified. For the previous version of this review we handsearched a further seven journals to 2002 and in August 2001 advertised the review in Vascular News, a newspaper for European vascular specialists. SELECTION CRITERIA: Randomised trials and non-randomised studies comparing carotid endarterectomy under local versus general anaesthetic. DATA COLLECTION AND ANALYSIS: Two review authors assessed trial quality and extracted the data independently. MAIN RESULTS: Nine randomised trials involving 812 operations, and 47 non-randomised studies involving 24,181 operations were included. Meta-analysis of the randomised studies showed that there was no evidence of a reduction in the odds of operative stroke, but the use of local anaesthetic was associated with a significant reduction in local haemorrhage (odds ratio 0.30, 95% confidence interval 0.12 to 0.77) within 30 days of the operation. However, the randomised trials were too small to allow reliable conclusions to be drawn, and in some studies intention-to-treat analyses were not possible because of exclusions. Meta-analsis of the non-randomised studies showed that the use of local anaesthetic was associated with significant reductions in the odds of stroke (38 studies), death (42 studies), stroke or death (27 studies), myocardial infarction (27 studies), and pulmonary complications (seven studies), within 30 days of the operation. The methodological quality of the non-randomised trials was questionable. Thirteen of the non-randomised studies were prospective and 36 reported on a consecutive series of patients. In eleven non-randomised studies the number of arteries, as opposed to the number of patients, was unclear. AUTHORS' CONCLUSIONS: There is insufficient evidence from randomised trials comparing carotid endarterectomy performed under local and general anaesthetic. Non-randomised studies suggest potential benefits with the use of local anaesthetic, but these studies may be biased.